Meaning of The Black Heralds in the Context of Spanish-Language Poetry - Aguilar Aguilar, Santiago Cristian (2020)
I propose to patent the meaning of the book The Black Heralds in the context of Spanish-language poetry from its time to the present day, through an amazing existential poetic legacy whose transcendence, one hundred years after its appearance in studies such as the one that summons us now, continues to explore the vital and human scope of the transcendent and singular poetic adventure of César Vallejo through his first poetic text in which the collective imaginary of the Andean cosmovision initiates its incorporation and forever to universal literature.